Pertanggungjawaban Pidana Terhadap Perbuatan Gratifikasi Dalam Tindak Pidana Korupsi (Studi Putusan No : 35/Pid.Sus.Tpk/2016/PN. Mdn) - Mangantar Anugrah Siregar; Rizkan Zulyadi; Riswan Munthe (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Gratuity is a new thing in the criminal act of corruption. Changes made to the previous regulation aim at overcoming the many modes and series of actions of civil servants and state administrators that have an impact on state financial losses and public welfare. The research method used is a normative method and this research is analytical descriptive. Regulations on acts of gratuity in corruption and criminal liability given by judges based on decision number: 35 / Pid.Sus.TPK / 2016 / PN.Mdn. Laws and regulations governing gratification have been set out in Article 12 B of Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning Eradication of Corruption, Factors for Acceptance of Gratuity due to greed, organization, and conflict of interests of civil servants or state administrators, and criminal liability given by the judges based on their considerations have considered mitigating and burdensome matters as well as paying attention to the absence of justification and forgiveness for imposing penalties in the form of imprisonment for 5 years and a fine of Rp. . 200,000,000 towards the perpetrators.